Cognitive‐motor profile, clinical characteristics and diagnosis of CHARGE syndrome: An Italian experience. Issue 12 (24th September 2014) - Santoro, Lucia; Ficcadenti, Anna; Zallocco, Federica; Baldo, Giada Del; Piraccini, Francesca; Gesuita, Rosaria; Ceccarani, Patrizia; Gabrielli, Orazio
<x xml:space="preserve">Abstract</x> Since 2005, the Pediatric Clinic of Maternal‐Infantile Sciences Institute in Ancona, in collaboration with the Lega del Filo d'Oro in Osimo, has been taking care of 35 patients with clinical and molecular diagnosis of CHARGE syndrome. Our investigation is the largest Italian cohort study of CHARGE patients. CHARGE syndrome is a multiple malformation syndrome involving ocular coloboma, heart defects, choanal atresia, retardation of growth and\or development, genital anomalies and\or urinary and ear abnormalities which leads to visual–auditory disabilities, cognitive impairment and behavioral abnormalities. Our purpose is to expand the knowledge of this syndrome by reviewing this group of affected patients in order to delineate in detail the natural history of the disease, and in particular to define the cognitive and motor profiles using an Italian questionnaire called "Progress Guide". Our main results show that Italian CHARGE patients have more delayed development in their physical abilities or skills with respect to normal patients. In particular, the delay is statistically significant in regard to self‐care skills (worse toileting, better washing) and the communication skill (language). On the other hand, the expressive skills are still preserved. When patients are considered according to their age (≤3 years) and (>3 years), the older ones have more delayed development than the younger ones when compared with healthy individuals of the same age. © 2014 Wiley Periodicals, Inc.